Branqueamento de Palythoa caribaeorum (Cnidaria, Anthozoa) em locais com diferentes impactos antrópicos na APAMLN e na ESEC Tupinambás (Ubatuba - SP, Brasil) - Bueno, Amanda Escarabichi [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Multiple natural and human stressors can affect the health of zoanthids, inducing several adverse effects such as bleaching. The zoanthid Palythoa caribaeorum is an important structurer of the benthic community and occurs on a large scale at rocky reefs across the Southeastern Brazil. There is no previous information on the health of zoanthids on the rocky reefs of marine protected areas in Ubatuba (SP, Brazil), despite the importance of such information for decision-making on marine conservation. This study aimed to monitor the percentage and degree of P. caribaeorum bleaching in places with different degrees and types of anthropic impacts in Ubatuba: Praia do Lázaro, Praia do Flamengo, Ilha das Couves, and Ilha das Palmas (control). The coverage of zoanthids was sampled in the summer, winter, and spring of 2021, along 25m transects, in which photos were taken considering the area determined by a sample square. Water samples were collected in each site for physicochemical analysis. Temperature data and degree heating weeks (DHW) values were obtained by satellite data. Human activities capable of affecting the colony's health were identified, and the relative environmental pressure index (REPI) was calculated. The polyp's colors were analyzed based on the Coral Health Chart. Ilha das Couves was the worst scenario in the summer, with the highest value of REPI (27.75). There was a decrease in bleaching of Ilha das Couves and the transect 2 of Praia do Flamengo throughout the seasons. Ilha das Palmas did not present significant differences from the other sites and had high bleaching percentages. With exception of Ilha das Palmas, a probable combination of anthropic effects and accumulation of thermal anomalies was the cause of bleaching. These same factors have been previously associated with bleaching events in the region. The results indicate the need for monitoring and studies in the rocky reefs of Ubatuba.

Múltiplos estressores, naturais e antrópicos podem afetar a saúde dos corais e zoantídeos, causando diversos efeitos, como o branqueamento. O zoantídeo Palythoa caribaeorum é um importante estruturador da comunidade bentônica e ocorre em larga escala nos recifes rochosos da região Sudeste do Brasil. Não há informação sobre a saúde dos zoantídeos nos costões rochosos de áreas marinhas protegidas em Ubatuba (SP, Brasil), sendo que esses dados são importantes para subsidiar a tomada de decisões. O estudo tem como objetivo monitorar a porcentagem e o grau de branqueamento da cobertura do zoantídeo Palythoa caribaeorum em locais com diferentes graus e tipos de impactos antrópicos em Ubatuba, sendo eles a Praia do Lázaro, Praia do Flamengo, a Ilha das Couves e a Ilhas das Palmas (controle). A cobertura do zoantídeo foi amostrada no verão, inverno e primavera de 2021, ao longo de transectos de 25m, nos quais fotos foram feitas utilizando um quadrado amostral. Coletas de água foram realizadas em cada praia, para análises físico-químicas. Valores de temperatura e degree heating weeks (DHW) foram obtidos por dados de satélites. Para cada área, foram identificadas as atividades humanas potencialmente capazes de afetar a saúde das colônias, e a partir disso foi calculado um Índice de Pressão Ambiental Relativa. A coloração dos pólipos foi analisada com base no Coral Health Chart. A Ilha das Couves foi o pior cenário encontrado no verão, com maior valor de REPI (27,75). Houve uma melhora no cenário da Ilha das Couves e do transecto 2 da Praia do Flamengo ao longo das estações. A Ilha das Palmas não apresentou diferenças significativas dos demais locais, apresentando também altas porcentagens de branqueamento. Com exceção da Ilha das Palmas, foi observado uma provável combinação de efeitos antrópicos com a acumulação de anomalias térmicas como causa do branqueamento. Sendo que esses mesmos fatores já foram antes associados a eventos de branqueamento na região. Os resultados obtidos indicam a necessidade de monitoramento e estudos nos recifes rochosos de Ubatuba.
Palythoa caribaeorum (Cnidaria, Anthozoa) bleaching in sites with different anthropic impacts in APAMLN and ESEC Tupinambás (Ubatuba - SP, Brazil)
Keywords: Zoantídeos; Recifes rochosos; Múltiplos estressores